(untitled) (Journal of Rashid Latif Medical College, 2025)
Background: Tetanus remains a life-threatening yet preventable disease, particularly in low- and middle-income countries. Despite global efforts, its burden persists among children due to insufficient immunization coverage, lack of booster doses, and poor awareness of post-exposure prophylaxis. In Pakistan, these challenges continue to contribute to morbidity and mortality associated with post-neonatal tetanus. Aim: This study aimed to evaluate the frequency of risk factors, immunization coverage, and clinical outcomes among children diagnosed with tetanus beyond the neonatal period at a tertiary care center. Methods: Conducted in 2024, this prospective observational study took place at the University of Lahore Teaching Hospital. Pediatric patients aged 1 month to 15 years admitted with clinical tetanus were included. Variables such as age, gender, immunization status (including DTP and TT boosters), identifiable risk factors, duration of hospitalization, and final outcomes were analyzed using SPSS version 16. Results: Among 74 participants, 46 (62.2%) were boys and 28 (37.8%) girls. The mean age was 6.8 ± 3.2 years, with the highest prevalence in children aged 6–10 years (52.7%). Vaccination data revealed 51 (68.9%) children were unvaccinated; none had received booster doses or post-exposure prophylaxis. Trauma accounted for the majority of cases (34; 45.9%), followed by ear discharge (14; 18.9%) and piercing injuries (3; 4.1%). The risk factor remained unidentified in 23 (31.1%) cases. Mean hospital stay was 13.7 ± 11.2 days. A mortality rate of 20.3% (15 patients) was significantly linked with shorter hospital stays (p<0.001) and absence of vaccination (p=0.01). Conclusion: The study revealed significant gaps in routine immunization and post-injury tetanus prophylaxis. Implementation of booster vaccination and early identification of high-risk groups, such as those with otorrhoea, is essential for prevention.